Association Between Length of Only-Child Period During Early Childhood and Overweight at Age 8—A Population-Based Longitudinal Study in Japan - Katagiri, Aomi; Nawa, Nobutoshi; Fujiwara, Takeo (Frontiers in Pediatrics, 2022)
Prior studies have shown that children who are the only child are more likely to be overweight compared to their peers with siblings, regardless of whether they are oldest, in the middle, or youngest. The study objective was to clarify whether there is an association between the length of the only-child period and the risk of overweight in firstborns who experienced an only-child period during early childhood before their siblings were born. 7,576 first-born boys and 7,229 first-born girls were examined from a nationwide longitudinal survey in Japan. Length of only-child period was determined by “birth interval”; i.e., the interval between birth of the index child and birth of the second child. It was categorized as short (less than 1.5 years), moderate (between 1.5 to 4 years), long (between 4 to 8 years), and only-child (the second baby was not born for 8 years). Overweight was defined as body mass index (BMI) z-score 1 standard deviation or more at age 8. Logistic regression was used to examine the association between length of only-child period and childhood overweight, adjusting for covariates. Moderate birth interval was inversely associated with being overweight in comparison with only-child in both boys (odds ratio (OR): 0.83, 95% confidence interval (CI), 0.72-0.96) and girls (OR: 0.75, 95% CI, 0.63-0.88). Long birth interval also showed inverse association in boys (OR: 0.78, 95% CI, 0.62-0.97), and marginal inverse association in girls (OR: 0.80, 95% CI, 0.62-1.04). First-born children who experienced short birth interval did not show different overweight risk from only-child. First-born children who experienced 1.5 to 8 years of birth interval had a lower risk of childhood overweight compared with only-child.